The longitudinal course of sleep timing and circadian preferences in adults with bipolar disorder. (19th December 2014) - Seleem, Mohammad A; Merranko, John A; Goldstein, Tina R; Goldstein, Benjamin I; Axelson, David A; Brent, David A; Nimgaonkar, Vishwajit L; Diler, Rasim S; Sakolsky, Dara J; Kupfer, David J; Birmaher, Boris
<x xml:space="preserve">Abstract</x> Objectives To study the longitudinal course of sleep timing and circadian preferences in individuals with bipolar disorder (BP) compared to individuals with non‐BP psychopathology and healthy controls. Methods Individuals with bipolar I and bipolar II disorder (n = 257), non‐BP psychopathology (n = 105), and healthy controls (n = 55) (mean age 40.2 years, 21.3% male, 85.1% Caucasian) were followed on average every 27 months for a mean of four years. Sleep timing parameters and circadian preference were reported using the Sleep Timing Questionnaire and The Composite Scale for Morningness. Group comparisons were adjusted for multiple comparisons and between‐group differences in demographic variables and psychopharmacological treatment. Results Regardless of their current mood state, individuals with BP showed more sleep onset latency (SOL), wakening after sleep onset (WASO), and evening preference in comparison to both individuals with non‐BP psychopathology and healthy controls. Individuals with BP also showed less stability of bed and awakening times in comparison to the other two groups, though these results were dependent on mood state. Non‐BP individuals only showed more WASO and less stability in bed and awakening times before work/school days than healthy controls. Adjusting for comorbid disorders yielded similar results. Within‐group analyses found little to no effect of time and BP subtype on sleep timing and circadian preference. Conclusions Disturbances of sleep timing are prominent in individuals with BP. These disturbances are worse during mood episodes, but still apparent during euthymic periods. Evening preference was not associated with polarity type, or mood state in BP, suggesting that this characteristic may be a trait marker.